Medicinal plants cultivated in urban home gardens in Heredia, Costa Rica - Roxana González-Ball; Tania Bermúdez-Rojas; Marilyn Romero-Vargas; Melissa Ceuterick (BMC, 2022)
Abstract Background Urban ethnobotanical research in Costa Rica is rather rare and home gardens are poorly studied so far. Investigating their biodiversity is crucial in gathering knowledge on the uses of this particular flora, especially related to the owners' health. This study therefore explores the diversity and knowledge of medicinal plants of private garden owners from three different urban neighborhoods in Heredia, Costa Rica, an thus far understudied area. Methods Semi-structured interviews (n = 61) were conducted with garden owners in three socioeconomically different urban neighborhoods (Central Heredia, Maria Auxiliadora and Bernardo Benavides). Information was collected about medicinal plants cultivated in the garden, treatments, plant part used and mode of administration. All species were identified and their geographical origin was determined. This information was then compared with the available regional and local (ethno)pharmacopoeias to detect possible newly documented uses. Results The majority or 90% of garden owners who also held knowledge on medicinal plants species were women﻿ (n = 30) of all ages (between 26 and 85 years old). A list of 27 species of medicinal plants was obtained from the participants of three urban neighborhoods. In Central Heredia, 74% (n = 20) of the total species were present, in Maria Auxiliadora 33% (n = 9) and in Bernardo Benavides 56% (n = 15). Most plant species were used by the participants to treat respiratory problems (11 spp.), hair and skin problems (9 spp.) and digestive disorders (8 spp.). Some plants were used to treat multiple ailments (10 spp.). About a third of all species (n = 8) were used by the participants to treat disorders that were not indicated in the regional and local pharmacopoeias. More specifically, Aloe saponaria, Blechum pyramidatum, Costus scaber, Impatiens walleriana, Lippia alba, Tradescantia zebrina, Psidium friedrichsthalianum and Solenostemon scutellarioides used for medicinal purposes by the participants were not found in the above-mentioned resources. Conclusions The present study provides new information about the use of medicinal plants in a thus far understudied urban area in Costa Rica. We documented new medicinal uses for several plants listed in the regional and local pharmacopoeias as well as for plants not previously reported in an urban environment. In general, there is little information about the types of plants used for medicinal purposes in urban ecosystems in Costa Rica. Although the country has a high endemic diversity of plants, many exotic medicinal plant species were introduced by the Spaniards during the colonization and by Afro-Costa Rican descendants. The present results thus show how the diversity of the medicinal plants used by these garden owners' confirms a socioeconomic gradient and reflects both Costa Rica's colonial history as well as the current epidemiological profile of the country. These findings underline the need for more ethnobotanical research in urban areas in Costa Rica.